Narrative truthiness : the logic of complex truth in hybrid (non)fiction - Wiese, Annjeanette (Frontiers of narrative., 2021)
Narrative Truthiness presents a new model for understanding truth and shows how a specific vein of postmodern writing engages with the overall goal of enhancing our interpretations of the complexities of the human experience.